Endoscopic Endonasal Reconstructive Methods to the Anterior Skull Base - Chakravarthi, Srikant; Gonen, Lior; Monroy-Sosa, Alejandro; Khalili, Sammy; Kassam, Amin (Seminars in Plastic Surgery, 2017)
The success of expanded endoscopic endonasal approaches (EEAs) to the anterior skull base, sellar, and parasellar regions has been greatly aided by the advancement in reconstructive techniques. In particular, the pedicled vascularized flaps have been developed and effectively cover skull base defects of varying sizes with a significant reduction in postoperative CSF leaks. There are two aims to this review: (1) We will provide our current, simplified reconstruction algorithm. (2) We will describe, in detail, the relevant anatomy, indications/contraindications, and surgical technique, with a particular emphasis on the nasoseptal flap (NSF). The inferior turbinate flap (ITF), middle turbinate flap (MTF), pericranial flap (PCF), and temporoparietal fascial flap (TPFF) will also be described. The NSF should be the primary option for reconstruction of majority of skull base defects following endonasal endoscopic surgery. In general, for the planum, cribriform, and upper two-thirds of the clivus, the NSF is ideal. For the lower-third of the clivus, the NSF may not be adequate and may require additional reconstructive options. Although limited in reach or more technically challenging, these reconstructive flaps should still be considered and kept in the surgical algorithm.
Keywords: expanded endoscopic endonasal approach; cerebrospinal fluid; nasoseptal flap; middle turbinate flap; inferior turbinate flap; pericranial flap; temporoparietal fascial flap